1988
DOI: 10.1111/j.1095-8649.1988.tb05457.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alarm substance and shoal size on the behaviour of zebra danios, Brachydanio rerio (Cyprinidae)

Abstract: Timidity, vigilance and response to alarm substance were examined in shoals consisting of one to 12 zebra danios, Brachydnnio rerio. Measures of timidity were not clearly related to shoal size.Fish in larger shoals spent more time in central areas of the tank away from cover than fish in smaller shoals. However, fish in small shoals appeared to be as aggressive as those in larger shoals. Vigilance and foraging rates did not appear to be related to shoal size. Per capita foraging rates and shoal size were not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…A decreased tendency to leave the shoal is regarded as a measure of reduced boldness (Moretz et al, 2007), which is a behavior connected to stress sensitivity in fish. In line with this, alarm pheromone exposure increases shoal cohesion in zebrafish (Rehnberg and Smith, 1988). Thus, a component of stress response could be involved in our results, although the way the experiment is performed, using the novel tank test as an acclimation period to the new environment, should decrease the stress impact.…”
Section: Discussionsupporting
confidence: 48%
“…A decreased tendency to leave the shoal is regarded as a measure of reduced boldness (Moretz et al, 2007), which is a behavior connected to stress sensitivity in fish. In line with this, alarm pheromone exposure increases shoal cohesion in zebrafish (Rehnberg and Smith, 1988). Thus, a component of stress response could be involved in our results, although the way the experiment is performed, using the novel tank test as an acclimation period to the new environment, should decrease the stress impact.…”
Section: Discussionsupporting
confidence: 48%
“…For example, in laboratory experiments, members of larger groups of cyprinids began foraging more quickly (Morgan & Colgan 1987), spent less time in cover or in evasive manoeuvres , and continued to feed longer in the presence of a model predator (Magurran et al 1985; but see Rehnberg & Smith 1988 for contradictory results). Similarly, Hill (1989) found that rosyside dace in an artificial stream would not forage unless at least four individuals were present in the stream together (in the absence of predators), suggesting that dace were less timid in larger groups.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish has an innate behavior to form schools and this partnership is related with predator avoidance, foraging, and mating [25,48,49]. In a situation that may generate anxiety in zebrafish, for example the attack of a predator, the group response is to increase social cohesion possibly as an adaptive group behavior to respond more adequately to stressors [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebrafish have a natural tendency to initially remain at the bottom of a novel environment (e.g., a test tank) and then gradually, over a few minutes, explore the higher portions of the test tank [25,27]. The anxiety response of zebrafish also includes forming stronger shoal cohesion and freezing [7,28,67]. Besides, Gerlai et al [28] reported that increased color intensity was associated with aggressiveness.…”
Section: Introductionmentioning
confidence: 97%